1986
DOI: 10.1083/jcb.103.5.1883
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural colocalization of tyrosinated and detyrosinated alpha-tubulin in interphase and mitotic cells.

Abstract: Abstract. Immunofluorescence with specific peptide antibodies has previously established that tyrosinated (Tyr) and detyrosinated (Glu) tubulin, the two species generated by posttranslational modification of the COOH-terminus of a-tubulin, are present in distinct, but overlapping, subsets of microtubules in cultured cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 20 publications
9
63
0
Order By: Relevance
“…1, short detyr-tubulin sections of up to 1 mm long were disrupted by longer segments of tyr-tubulin, thus leading to a string-of-pearls-like appearance of the two tubulin variants with a preferential concentration of tyr-tubulin at the tubulus ends. Similar arrangements of interspersed detyr-and tyr-tubulin stretches had been seen for interphase and metaphase microtubules using immuno-EM (Geuens et al, 1986). However, antibodies directed against a-tubulin as a control were more or less evenly distributed along microtubules (supplementary material Fig.…”
Section: Distribution Of Detyrosinated and Tyrosinated Tubulin In Polsupporting
confidence: 61%
See 1 more Smart Citation
“…1, short detyr-tubulin sections of up to 1 mm long were disrupted by longer segments of tyr-tubulin, thus leading to a string-of-pearls-like appearance of the two tubulin variants with a preferential concentration of tyr-tubulin at the tubulus ends. Similar arrangements of interspersed detyr-and tyr-tubulin stretches had been seen for interphase and metaphase microtubules using immuno-EM (Geuens et al, 1986). However, antibodies directed against a-tubulin as a control were more or less evenly distributed along microtubules (supplementary material Fig.…”
Section: Distribution Of Detyrosinated and Tyrosinated Tubulin In Polsupporting
confidence: 61%
“…In MDCK cells, both the tyrosinated and detyrosinated isoforms were present along most of the length of double positive microtubules with alternating sections of the two isoforms. Segmental labelling of microtubules has been described previously (Geuens et al, 1986;Webster et al, 1987). Detyrtubulin stretches can be generated by an individual turnover from tyr-to detyr-tubulin, which is facilitated on pre-existing microtubules (Arce and Barra, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that domains of acetylation occurred on stable MTs (Webster and Borisy, 1989), suggesting that this modification differentiated particular MT regions for specific functions. Similarly, detyrosination, which accumulates uniformly on MTs (Geuens et al, 1986), may mark entire MTs for functional specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Detyrosination occurs after incorporation of tubulin subunits into the microtubule lattice (Kumar and Flavin, 1981) on diverse microtubules (Geuens et al, 1986;Gundersen and Bulinski, 1986;Gundersen et al, 1984;Johnson, 1998;Webster et al, 1987). Detyrosination is likely to be generated by the cytosolic carboxypeptidase 1 (CCP1, also known as NNA1), a finding based on the observation that a mutation in Ccp1 in mice greatly decreases the level of microtubule detyrosination (Kalinina et al, 2007).…”
Section: C-terminal Proteolytic Events Of -Tubulin -Detyrosination Amentioning
confidence: 99%